Trait self-esteem and claimed self-handicapping motives in sports situations - Finez, L.; Berjot, S.; Rosnet, E.; Cleveland, C.; Tice, D. M. (Journal of Sports Sciences, 2012)
We examined the relationship between physical self-esteem and claimed self-handicapping among athletes by taking motives into consideration. In Study 1, 99 athletes were asked to report their tendency to engage in claimed self-handicapping for self-protective and self-enhancement motives (trait measures). Low self-esteem athletes reported a higher tendency to engage in claimed self-handicapping for these two motives compared with high self-esteem athletes. Neither low nor high self-esteem athletes reported a preference for one motive over the other. In Study 2, 107 athletes participated in a test that was ostensibly designed to assess high physical abilities - and thus to encourage self-handicapping for self-enhancement motives (success-meaningful condition) - or to assess low physical abilities, and thus to encourage self-handicapping for self-protective motives (failure-meaningful condition). Before starting the test, athletes were given the opportunity to claim handicaps that could impair their performance. Low self-esteem athletes claimed more handicaps than high self-esteem athletes in both conditions. Findings suggest that low physical self-esteem athletes engage more in claimed handicapping regardless of motives, relative to high physical self-esteem athletes.